Blurring Boundaries: Exploring the Cultural Identity Intersection of Teachers - Akmal Mundiri; Juwita; Rahimah Embong (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
Teachers' cultural identities in educational practice often do not fully reflect their original ideologies, but rather merge with local identities through complex social interactions. This study aims to examine how teachers with Nahdlatul Ulama (NU) backgrounds negotiate their cultural identities in the context of Muhammadiyah schools through a process of blurring boundaries. This study aims to understand the representation of teachers' identities within the work culture of schools with mismatched beliefs. This study used a qualitative approach with a case study approach. Data were collected through interviews, observation, and documentation. The collected data were analyzed using Miles and Huberman's data analysis techniques, which consist of data reduction, data display, and verification. The results indicate that the representation of teachers' identities within the work culture of NU teachers in Muhammadiyah schools involves the negotiation of teachers' cultural identities in religious practices, the flexibility of language and symbols in learning communication, and the teachers' spiritual professionalism and social intelligence in a pluralistic environment. Thus, identity negotiation occurs harmoniously without conflict, as teachers adapt their worship practices, symbols, and communication styles to Muhammadiyah institutional standards while maintaining their personal identities in the private sphere. This negates the notion that teacher identity within the teacher work culture is a form of religious identity negotiation, a form of harmoniously negotiated religious identity within a pluralistic Islamic institution through symbolic practices, communication, and value development.